Advances in Adipose-Derived Stem Cells Isolation, Characterization, and Application in Regenerative Tissue Engineering - Umesh D. Wankhade; Michael Shen; Ravindra Kolhe; Sadanand Fulzele (Hindawi Limited, 2016)
Obesity is a complex, multifactorial disease that has been extensively researched in recent times. Obesity is characterized by excess deposition of adipose tissue in response to surplus energy. Despite the negative connotations of adipose tissue (AT), it serves as a critical endocrine organ. Adipose tissue is a source of several adipokines and cytokines which have been deemed important for both normal metabolic function and disease formation. The discoveries of metabolically active brown AT in adult humans and adipose tissue derived stem cells (ADSC) have been key findings in the past decade with potential therapeutic implications. ADSCs represent an enticing pool of multipotent adult stem cells because of their noncontroversial nature, relative abundance, ease of isolation, and expandability. A decade and a half since the discovery of ADSCs, the scientific community is still working to uncover their therapeutic potential in a wide range of diseases. In this review, we provide an overview of the recent developments in the field of ADSCs and examine their potential use in transplantation and cell-based therapies for the regeneration of diseased organs and systems. We also hope to provide perspective on how to best utilize this readily available, powerful pool of stem cells in the future.